Analysing genetic information with DNA arrays. - Case-Green, S; Mir, K; Pritchard, C; Southern, E (1998)
The large amount of DNA sequence information produced in recent years has created a need for high-throughput methods in biology and genetics. These include sequencing, comparing gene sequences and genotyping. DNA arrays promise a highly parallel means for analysis of DNA that is fast and cost-effective, and offers scope for application to complex systems and processes. Recent years have seen continued transfer of technology from the microelectronics industry. Rapid application of the technology to genotyping, antisense oligonucleotide selection and gene expression analysis has illustrated the general power of this approach.